The Role of Physical Activity in the Rehabilitation of Children with Fetal Alcohol Syndrome: Why It Should Be Considered a Vital Part of Treatment - Dyląg, Liliana; Graca, Magdalena; Szopińska, Kinga; Łowicka, Weronika; Wawszkowicz, Konrad; Oluszczak, Karolina; Szeliga, Anna; Korta, Karolina; Szostak, Agata; Śmigielska-Mikołajczyk, Maria Janina (Quality in Sport, 2024)
This literature review examines the pivotal role of physical activity in the treatment and rehabilitation of children with Fetal Alcohol Syndrome (FAS). By analysing a range of research studies, this review identifies the beneficial impact of structured physical activity programmes on motor skills, cognitive functions, and behavioural outcomes in children with FAS. Furthermore, it proposes educational recommendations for integrating physical activity into therapeutic interventions.